(untitled) (American Journal of Islam and Society, 2006)
London and New York: I.B. Tauris and Oxford University Press India, in association with the Oxford Centre for Islamic Studies, 2004. 159 pages. In the “Foreword,” Michael Carter states that his book is aimed at the general reader who is interested in the history of Arabic grammar and, in particular, in the achievement of Sibawayhi, the discipline’s architect and originator. This much-needed and long-awaited effort is a welcome addition to the field of Arabic grammatical theory, for it contextualizes Sibawayhi’s grammatical ideas, as set forth in his Al-Kitab, by giving a short account of his background and life (p. vii). The reader, whether advanced or novice, will appreciate how accessible the material has been made. To be sure, reducing Sibawayhi’s complex and profound observations to 145 pages runs the risk of making it even harder to understand. But the author avoids such pitfalls with ease and grace. In fact, a knowledge of Arabic is not essential; but, as the author says, “given the nature of the topic it will certainly be useful” (p. vii). All examples are transliterated and translated, and technical terms and basic concepts are explained as often as possible. Despite the complex subject matter, Carter does a brilliant job describing the Kitab’s place within the Arabo-Islamic system and the historical context in which it was written. It is useful to spend some time on Sibawayhi’s life, even though little is actually known about it, and so chapter 1, “Sibawayhi the Person,” explores his importance through portraits in biographies as well as from the contents of his own work. It has been convincingly argued that the earliest form of Sibawayhi’s name (Amr ibn `Uthman Sibawayhi) is probably authentic (p. 9). That Sibawayhi was by origin a Persian who ended up in Basra seems to be beyond contention, although neither the date nor the place of his birth can be confirmed. All biographies agree that he came to Basra to study religious law, either Hadith (traditions of the Prophet) or basic principles of fiqh (jurisprudence), which were just beginning to take form. The details of his death are just as vague as those of his birth and personal history. Carter presents his readers with a short account of this problem, with which even the classical biographers had to wrestle (see pp. 15-16) ...